2012
DOI: 10.1016/j.metabol.2012.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported speed of eating and 7-year risk of type 2 diabetes mellitus in middle-aged Japanese men

Abstract: Short page-heading: Speed of eating and incidence of diabetes Text, 2,551 words, Abstract 249 words; number of References, 33; number of Tables, 3. Conflict-of-interest disclosure: None. AbstractObjective: This cohort study investigated the association between eating speed and the incidence of type 2 diabetes in middle-aged Japanese men. Materials/Methods: Participants were 2,050 male employees of a metal products factory in Japan. We measured self-reported categorical eating speed. The incidence of diabetes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
74
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 33 publications
7
74
0
3
Order By: Relevance
“…The subjects in the present study who assessed themselves as fast eaters tended to be overweight and obese, and indeed ate the test meal with a smaller total number of chews and shorter total meal duration than did the slow eaters. This is consistent with the findings of many previous studies of the relationships between the objectively and subjectively assessed eating speeds and the body composition and shape (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Previous studies have also demonstrated that fast eating induces overeating, and that overeating is related to weight gain due to the ingestion of a larger volume of food before experiencing satiety (22)(23)(24).…”
supporting
confidence: 92%
See 3 more Smart Citations
“…The subjects in the present study who assessed themselves as fast eaters tended to be overweight and obese, and indeed ate the test meal with a smaller total number of chews and shorter total meal duration than did the slow eaters. This is consistent with the findings of many previous studies of the relationships between the objectively and subjectively assessed eating speeds and the body composition and shape (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Previous studies have also demonstrated that fast eating induces overeating, and that overeating is related to weight gain due to the ingestion of a larger volume of food before experiencing satiety (22)(23)(24).…”
supporting
confidence: 92%
“…Cross-sectional, longitudinal and experimental studies have provided strong evidence for fast eating inducing overweight (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The subjects in the present study who assessed themselves as fast eaters tended to be overweight and obese, and indeed ate the test meal with a smaller total number of chews and shorter total meal duration than did the slow eaters.…”
mentioning
confidence: 50%
See 2 more Smart Citations
“…Thus, eating slowly per se does not affect postprandial glucose or gastrointestinal hormone levels directly in patients with type 2 diabetes. Indeed, the speed of eating was associated with the incidence of type 2 diabetes, but associations between eating speed and the incidence of diabetes were not significant in models with additional adjustment for BMI [29] . Therefore, eating slowly prevents excess energy intake and body weight gain over a long observation period and may improve insulin resistance and glycemic control in patients with type 2 diabetes.…”
Section: Patients With Diabetes (Including Our Data)mentioning
confidence: 91%